LEV SEMIONOVICH VYGOTSKY - Caravieri Teixeira, Patrícia (Revista Coleta Científica, 2021)
The work LEV SEMIONOVICH VYGOTSKY, by Ivan Ivic, is part of the Educators Collection, which brings together a select group of renowned educational thinkers from national and international spheres; grouping some of the main exponents in the history of education. It is a work that has a special focus on concepts relevant to education, selected by Ivic and presented to readers under his elaborate interpretation.